Desempenho de bovinos e emissão de metano em Sistemas Silvipastoris em regiões de clima tropical - Alan Figueiredo de Oliveira (2023)
Silvopastoral systems (SSPs) can reconcile high levels of production and environmental preservation, which makes it essential to define practical recommendations for their implementation and the environmental impact of these systems. This study aimed (i) to compare the enteric methane emission and the performance of dairy cows grazing integrated systems in Brazil, (ii) to evaluate the pasture characteristics and the performance of cattle in SSPs with Eucalyptus and Urochloa through systematic review and meta-analysis and (iii) to evaluate the effect of shading on tropical grass traits and cattle performance in SSPs through systematic review and meta-analysis. In the first experiment, eighteen Holstein-Zebu cows were randomly assigned to a crop-livestock integration system (CLI) or a crop-livestock-forest integration system (CLI) to determine milk production, feed efficiency, consumption and methane emission. Milk production and feed efficiency were similar between systems. Energy loss and methane emission were the same between the systems, which shows that there are no significant differences between the systems. In the second experiment, systematic searches in databases found 2,639 articles, of which 29 (120 comparisons) evaluated SSPs with Eucalyptus spp. and Urochloa spp. were selected. The forage mass was higher in the SSPs with up to 99 trees/ha and lower with the other densities in relation to the pasture in monoculture. Forage mass was lower in SSPs with all spacing between tree lines and planting orientations in relation to pasture in monoculture, with lower forage mass being observed with smaller spacing and with north-south planting orientation. Total weight gain per area (GPT) was lowest in SSPs with less than 28m between rows of trees or with more than 199 trees/ha, but was higher in SSPs with more than 28m between rows or with up to 99 trees/ha in comparison with pasture in monoculture. GPT was lower in SSPs with north-south planting orientation compared to monoculture pasture, but was equal in east-west orientation. In the third experiment, 66 articles were selected with all types of tropical trees and grasses. There was a small reduction in forage mass in SSPs with 9 leguminous trees, but weight gain per area was similar to pasture in monoculture. The animals also had higher dry matter intake, crude protein intake and milk production in these SSPs with leguminous trees. Tropical grasses in SSPs with palm trees showed higher crude protein, lower forage mass and there was no reduction in GPT compared to pasture in monoculture, which indicates the possibility of animal production together with palm trees. SSPs with other tree types had higher GPT compared to pasture in monoculture. This result indicates that the use of SSPs with native trees can integrate animal production with environmental preservation. SSPs with greater or similar weight gain per area compared to monoculture pasture can increase total system production and profitability.